IS GLOBAL MINIMUM TAX (GMT) BENEFICIAL FOR DEVELOPING COUNTRIES? REFLECTIONS FROM AN INDONESIAN PERSPECTIVE - Krisnandi, Putu Adela; Muttiwijaya, Gede Teguh Prasetya (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study examines whether the GMT benefits developing countries or mainly reinforces the taxing rights of developed economies, with Indonesia as the focal point given its reliance on FDI. Using a qualitative descriptive method and comparative policy analysis, the research synthesizes OECD projections, national FDI data, and sectoral cases to assess Indonesia’s revenue prospects and competitiveness under GMT. Findings show that while Indonesia may gain short-term revenue through the QDMTT, most benefits accrue to developed countries via the IIR. The declining effectiveness of tax incentives such as holidays requires Indonesia to strengthen non-tax competitiveness, particularly infrastructure, regulatory certainty, and skilled human capital. Robust domestic enforcement and stronger tax administration are also essential to secure expected revenue. The study contributes by linking global GMT debates to Indonesia’s case and interpreting outcomes through tax competition, dependency theory, and fiscal federalism, showing how GMT reshapes fiscal sovereignty in developing economies. Limitations include reliance on secondary data and the absence of micro-level evidence on multinational enterprises behavioral responses. Future research should address firm-level and sectoral data post-GMT to capture real investment shifts and evaluate alternative policy tools beyond tax incentives. Overall, this paper provides actionable insights for Indonesian policymakers to adapt fiscal strategies to the global tax landscape while sustaining long-term investment competitiveness.